ANALYSIS OF PROGRESS TEST RESULTS IN MEDICAL FACULTY STUDENTS - Ade Pryta Romanauli Simaremare (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2021)
Background: Assessment of learning outcomes is an important evaluation material to show how the teaching and learning process has been carried out. It can be obtained from formative and summative assessment, then students are given feedback from these results. One method for formative evaluation is a progress test. During the implementation at the HKBP Nommensen University Faculty of Medicine, there had never been an analysis of the results of the Progress Test activity. This study was conducted for analysing of the results of the Progress Test held in the even semester of the 2018/2019 academic year. Methods: This study used an observational descriptive design with cross sectional method. The sample were all students of the Faculty of Medicine who were actively studying in the even semester of the 2018/2019 Academic Year totaling 215 subjects. Item analysis was done on the questions for basic and clinical medicine category by the level of difficulty and the discrimination index based on students’ study period. Results: Students passing rate that attended the progress test in this study were very low. However, the score achieved by the students increased along with the length of students’ study period. Item analysis resulted the difficulty level majority at the medium level, and the discrimination index majority at the poor level for both the basic and clinical medicine science category. Conclusion: Progress testing can be used as a tool to help curriculum designer see the development of students’ knowledge skills both individually and in population.